Synthesis, spectral characterization and biological activity of Zn(II) complex with 2′-[1-(2-hydroxyphenyl)ethylidene]benzenesulfanohydrazide - Gwaram, Nura Suleiman; Musalam, Laila; Ali, Hapipah Mohd; Abdulla, Mahmood Ameen; Shaker, Shayma A. (Elsevier, 2012)
Zinc(II) complex with 2′-[1-(2-hydroxyphenyl) ethylidene] benzenesulfanohydrazide, was synthesized, and structurally characterized by elemental analysis CHN, TGA, UV, FT-IR, 1H NMR and 13C NMR spectroscopy. Its preventive effect on ulcer activity induced by absolute ethanol in Sprague–Dawley rats was studied in vivo. Gastric ulcers were induced in rats by administrating absolute ethanol. Twenty four Spragu–Dawley rats (12 males and 12 females) were assigned equally into the following 4 groups (n = 6): negative control; positive control; low dose, which received low oral doses of the compound; and high dose, which received high oral doses of the compounds . These animals were subjected to overnight fasting (food but not water) prior to dosing. Gastric wall mucus, ulcer areas and histology of gastric walls were assessed in addition gastric homogenate was determined for superoxide dismutase (SOD), glutathione (GSH) and malondialdehyde (MDA). Pre-treatment of rats with compound significantly prevented ethanol-induced gastric wall depletion and restored non-sulfhydryl (NP-SH) content in glandular stomachs. The Zinc(II) complex also exhibits high levels of SOD, and GSH enzymes as well as a reduced amount of lipid peroxidation enzyme, malondialdehyde. This study describes a model to produce extensive gastric necrosis in rats by induction with absolute ethanol. The administration of zinc(II) complex with benzensulfanohydrazone at 30 min before induction with absolute ethanol reduced or totally eliminated lesions.